Emergency cross-sectional radiology - Chung, Daniel Y. F. , 1982- (Cambridge University Press, 2012)
"Cross-sectional imaging plays an ever-increasing role in the management of the acutely ill patient. There is 24/7 demand for radiologists at all levels of training to interpret complex scans, and alongside this an increased expectation that the requesting physician should be able to recognise important cross-sectional anatomy and pathology in order to expedite patient management. Emergency Cross-Sectional Radiology addresses both these expectations. Part I demystifies cross-sectional imaging techniques. Part II describes a wide range of emergency conditions in an easy-to-read bullet point format. High quality images reinforce the findings, making this an invaluable rapid reference in everyday clinical practice. Emergency Cross-Sectional Radiology is a practical aide-memoire for emergency medicine physicians, surgeons, acute care physicians and radiologists in everyday reporting or emergency on-call environments" -- Provided by publisher.